KECERNAAN LEMAK DAN SERAT KASAR PAKAN ANAK KUDA PACU (YEARLING) INDONESIA YANG DIBERI PAKAN PENGUAT LOKAL DAN IMPOR - Mamahit, Kristian; Tulung, Y.L.R.; Rahasia, C.A.; Moningkey, S.A.E. (ZOOTEC, 2019)
CRUDE FIBER AND FAT DIGESTIBILITY OF INDONESIAN YEARLINGÂ LOCAL-RACING HORSE FED LOCAL AND IMPORTED CONCENTRATE. The objective of this study was to determine the ability of racing foals to digest feed both local and imported feed. This study was conducted at the Tonsewer Village, Tompaso District for 30 days consisting of preparation and data collection. The data were collected from type and amount of feed consumed by racing foals and the number of feces (head-1 day-1). The animals of 20 individuals at the ages of 13-24 months old were used in this study. The amount of 10 racing foals were fed local feed and the rests of 10 racing foals were fed imported feed.Â The variables measured were digestibility of crude fat and crude fiber, found as the difference between the feed substances consumed and those excreted in feces and divided by those consumed feed at 100%. The results showed that the average digestibility of crude fat for local feed was 66.16% and imported feed was 75.16%, respectively. The digestibility of local and imported raw fiber feed was 65.53% and 72.16%, respectively. Based on statistical analysis using the t-test showed that the digestibility of crude fiber and fat of imported feed was significantly different (P <0.05) compared to local feed. This might be due to higher content of the crude fat and crude fiber of imported feed than those of local feed.Keywords: Digestibility, fat, crude fiber Racing horses, local feed, imported feed.